The Impact of Degree of Doneness, Muscle Source, and Bloom Time on Cooked Color and Cooked Color Stability - Greta E. Huber; Taylor M. Dieball; Natalie T. Acosta Castellanos; Kiersten M. Gundersen; Kasey R. Maddock Carlin; Michael D. Chao; Jessie L. Vipham; Morgan D. Zumbaugh; Travis G. O'Quinn; Erin S. Beyer (Kansas Agricultural Experiment Station Research Reports, 2025)
Objective: This study examined the differences in color stability between three different muscles cooked to varying degrees of doneness by taking color readings at four different time points. Study Description: longissimus lumborum (LL), psoas major (PM), and semitendinosus (ST) were cooked to medium rare (MR), medium (MED), or well done (WD) degree of doneness (DOD). Color was measured at 0, 3, 6, and 9 minutes to observe color stability changes. Results: There was an interaction (P < 0.05) between DOD and muscle for L* (lightness) readings. The ST had the highest L* reading within the MR and MED DOD followed by the LL; however, there were no differences between muscles (P > 0.05) within the WD DOD. The 0-minute readings had a lower (P < 0.05) L* reading in comparison to 9 minutes, while not being different (P > 0.05) from 3 or 6 minutes. Similar to the L* readings, there was an interaction (P < 0.05) between DOD and muscle for a* readings. Within the MED DOD, the ST had the highest (P < 0.05) a* reading followed by the LL, while the LL had the highest (P < 0.05) a* reading within the MR and WD DOD. There was an interaction (P < 0.05) between DOD and muscle and DOD and time for the oxymyoglobin (OMb) percentage. Within the MR samples, the LL and ST muscles resulted in similar (P > 0.05) OMb percentage. The MR DOD had the highest (P < 0.05) OMb percentage for 3, 6, and 9 minutes while the 0-minute readings for MR and MED were similar (P > 0.05) and higher (P < 0.05) than all-time points for the WD DOD. The Bottom Line: : Muscle influences cooked color and its stability, so if there are significant differences among muscles, it might be necessary to provide consumers with specific cooking instructions for each muscle.
Keywords: beef; color stability; cooked color